Comprehensive analysis of the prognostic, immunological, and diagnostic roles of SIRT1 in pan-cancer and its validation in KIRC - Liu, Qi; Sun, Songxian; Zhou, Chunxiang; Xu, Houxi (Frontiers in Immunology, 2025)
BackgroundDisturbances in DNA damage repair may lead to cancer. SIRT1, an NAD+-dependent deacetylase, plays a crucial role in maintaining cellular homeostasis through the regulation of processes such as histone posttranslational modifications, DNA repair, and cellular metabolism. However, a comprehensive exploration of SIRT1’s involvement in pan-cancer remains lacking. Our study aimed to analyze the role of SIRT1 in pan-cancer to gain a more comprehensive understanding of its role in multiple malignancies.MethodsWe systematically examined the role of SIRT1 in pan-cancer by analyzing data from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. Various tools, including R, Cytoscape, HPA, Archs4, TISIDB, cBioPortal, STRING, GSCALite, and CancerSEA, were used to integrate and analyze SIRT1 gene expression, prognosis, protein interactions, signaling pathways, immune infiltration, and other relevant information. Furthermore, we validated the differential expression of SIRT1 in normal human kidney cells and kidney cancer cell lines via experimental verification.ResultsSIRT1 expression was significantly reduced in various cancers and was different across molecular and immune subtypes. SIRT1 is intricately linked to numerous cancer pathways. In most cancer types, increased SIRT1 expression is positively associated with eosinophils, helper T cells, central memory T cells, effector memory T cells, γδ T cells, and Th2 cells. SIRT1 expression is significantly correlated with immune regulatory factors across various cancer types. Quantitative reverse transcription polymerase chain reaction (qRT–PCR) and Western blot (WB) analyses confirmed that SIRT1 is differentially expressed in kidney renal clear cell carcinoma (KIRC).ConclusionsUsing an integrative approach involving bioinformatics analysis and experimental validation, we clarified the potential roles and mechanisms of SIRT1 in pan-cancer, providing a theoretical basis for the development of SIRT1-targeted therapies in clinical applications.